Changes in oral health-related quality of life before and after dental treatment in 8–12-year-old Costa Rican schoolchildren - Jiménez Lobo, Juliana Endrina (2023)
Aims: The aims of this study were to (1) evaluate oral health-related quality of life (OHRQoL) in 8–12-year-old Costa Rican schoolchildren before and after dental treatment and (2) collect clinical and sociodemographic characteristics. Methods: Schoolchildren completed the Child Oral Health Impact Profile-Short Form (COHIP-SF-19) questionnaire before and after dental treatment. One of the parents was asked to complete a sociodemographic survey. Patients were treated for caries, hypomineralizations, and dental malocclusions. The prevalence of these conditions were assessed from the patient’s electronic dental record. Results: Eighty participants (39 male and 41 female, average age: 9.4 ± 1.0 years) were recruited. The prevalence of dental caries was 56.1% with a mean deft and DMFT score of 3,15 ± 0.96 and 2.22 ± 0.77, respectively. Prevalence of hypomineralizations was 53.7% and dental malocclusions was 82.9%. The Simplified Oral Hygiene Index before treatment was 1.45 ± 0.45 and after was 1.42 ± 0.43. Mean COHIP-SF-19 total score decreased from 53,7 ± 7,8 before dental treatment to 31,4 ± 4,2 after treatment. Improvements in all subdomains were also observed. Regarding sociodemographic characteristics, 65% of the patients lived in San José, Costa Rica’s capital city, and 56.3% of the studied population belonged to a low-income family. Most parents did not complete high school. Regarding the number of family members living in the same house as the patient, an average of four people was reported. In relation to family structure, 58.8% of the children’s parents lived together, either married or free union. As for household owning, 53.8% of parents reported owning their house, 36.3% lived in a rented house, and 10% lived in a borrowed home. Conclusion: The prevalence of caries, hypomineralizations, and dental malocclusions were high before dental treatment. Reported sociodemographic characteristics unlikely changed after dental treatment, suggesting dental care played a pivotal role in improving self-perceptions of oral health and quality of life in our clinical setting.